Orbital stability of standing waves for supercritical NLS with potential on graphs. Issue 8 (10th June 2020) - Ardila, Alex H.
ABSTRACT: In this paper, we study the existence and stability of normalized standing waves for the nonlinear Schrödinger equation on a general starlike graph with potentials. Under general assumptions on the graph and the potential, we show the existence of orbitally stable standing waves when the nonlinearity is L 2 -critical and supercritical.